The effect of knowledge sharing and motivation on competence with innovative behavior as a mediator variable (study on teachers in East Jakarta) - Lidheawati Nuraini (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
Abstract Purpose: This study aims to determine how the influence of Knowledge Sharing and Motivation on Competence mediated by Innovative Behavior in teachers in East Jakarta. Methods: The research method used is a quantitative approach with data collection through google form. The population in this study were teachers in East Jakarta. The sampling technique in this study used purposive sampling technique with 100 respondents. Data analysis was performed using SEM (Structural Equation Modeling) with Smart PLS software to evaluate the relationship between variables. Findings: The results of the study prove that (1) Knowledge Sharing affects Innovative Behavior, (2) Motivation affects Innovative Behavior, (3) Knowledge Sharing affects Competence, (4) Motivation affects Competence, (5) Innovative Behavior affects Competence, (6) Innovative Behavior indirectly affects Knowledge Sharing on Competence, (7) Innovative Behavior indirectly affects Motivation on Competence.